+0  
 
0
424
1
avatar

how do you solve (3x+9)-(5x-0) 

side note: dont want just the answer but also how'd you solved the answer...

 Jun 5, 2014

Best Answer 

 #1
avatar+3451 
+8

Start by lining it up vertically.

   3X + 9

-  5X - 0   (then just subtract like you usuallly would)

------------

 -2X+9 

 

 So your answer is (-2X+9)

 

You can check this by putting in a number for x, for the simplified version and the original problem to see if it works. Let's put the number 5 in.

 

Original problem: 

(3(5)+9)-(5(5)-0) =

(15 + 9)-(25- 0) =

(24)-(25)

 = -1

 

Simplified version:

(-2(5)+9) =

((-10) + 9)

= -1

 

They both equal -1, so it works!

 Jun 5, 2014
 #1
avatar+3451 
+8
Best Answer

Start by lining it up vertically.

   3X + 9

-  5X - 0   (then just subtract like you usuallly would)

------------

 -2X+9 

 

 So your answer is (-2X+9)

 

You can check this by putting in a number for x, for the simplified version and the original problem to see if it works. Let's put the number 5 in.

 

Original problem: 

(3(5)+9)-(5(5)-0) =

(15 + 9)-(25- 0) =

(24)-(25)

 = -1

 

Simplified version:

(-2(5)+9) =

((-10) + 9)

= -1

 

They both equal -1, so it works!

NinjaDevo Jun 5, 2014

60 Online Users

avatar
avatar
avatar
avatar
avatar
avatar